LITERATURE REVIEW: SELF AWARENESS OF BADUY NONOMAN - Hakim, Ibrahim Al; Khairun, Deasy Yunika (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
This article aims to describe the self-awareness of Baduy nonoman (adolescents). This article uses a literature review method. Literature is obtained from various articles. The analysis unit in this article is written documents about self-awareness research in the form of journal articles and research reports through an online journal database.